Pica in a girl with non-suicidal self-injury: a case report - Liu, Bo; Jiang, Lijun; Yuan, Minlan; Zhu, Hongru; Zhang, Wei (Frontiers in Psychiatry, 2023)
Non-suicidal self-injury is on the rise globally, posing a significant societal challenge. Pica, an eating disorder, presents difficulties in treatment due to the absence of effective medications. In this report, we discuss a complex case involving the co-occurrence of pica and non-suicidal self-injury. A 13-year-old girl was admitted to our hospital due to ingesting two batteries. She features a persistent, intense appetite along with sudden and compulsive behaviors such as consuming inedible items or self-inflicted cutting. After receiving a combination of pharmacological treatments (quetiapine, lithium and sertraline), cognitive behavioral therapy (CBT) and modified electroconvulsive therapy (MECT) for 25 days, she was discharged with relief from her clinical symptoms.